2012
DOI: 10.4103/0971-3026.107179
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary stalk transection syndrome: Comparison of clinico-radiological features in adults and children with review of literature

Abstract: Hypo-pituitarism results from impaired production of one or more of anterior pituitary trophic hormones. A rare cause of hypo-pituitarism is pituitary stalk transection syndrome. The MRI features of this condition in children and its association with hormonal deficiencies have been reported earlier. Reports on adults with this disorder are scarce, with only one small case series published in the recent literature. We studied the hormonal deficiency pattern and MRI findings of 12 patients with pituitary stalk t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
1
22
0
4
Order By: Relevance
“…A possible explanation is that pituitary insufficiency may be caused by transient anoxia of the hypothalamus at the time of delivery (38,39). Another hypothesis is that anterior lobe hypoplasia and dysfunction result in decreased hormone secretion, which in turn causes increased incidence of breech presentation (20). Dystocia including caesarean or forceps is also present in PSIS patients.…”
Section: Perinatal Eventsmentioning
confidence: 99%
“…A possible explanation is that pituitary insufficiency may be caused by transient anoxia of the hypothalamus at the time of delivery (38,39). Another hypothesis is that anterior lobe hypoplasia and dysfunction result in decreased hormone secretion, which in turn causes increased incidence of breech presentation (20). Dystocia including caesarean or forceps is also present in PSIS patients.…”
Section: Perinatal Eventsmentioning
confidence: 99%
“…Furthermore, CISS obtained at submillimetric thickness can provide more detailed visualization of the suprasellar compartment due to good contrast between CSF and the surrounding structures. 26 While CISS imaging has been shown to be effective at predicting pituitary macroadenoma consistently, its ability to detect pituitary adenoma in CD patients has never been reported. 10,27 In our patient cohort, we found that CISS sequence had a similar, albeit slightly lower, sensitivity to CE-VIBE at detecting pituitary adenoma in CD patients (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Была сформулирована теория механического разрыва стебля гипофиза в момент родов за счет натяжения стебля и травмы в узком месте диафрагмы турецкого седла или возникающей ишемии данной области. По мере накопления клинических данных были описаны пациенты, рожденные в головном предлежании без сопутствующей гипоксии или рожденные путем кесарева сечения [6]. В настоящий момент высокий процент ягодичного предлежания среди пациентов с гипопитуитаризмом объ- ясняют врожденным дефицитом гормонов аденогипофиза или дефицитом других факторов, приводящих к снижению двигательной активности плода [6].…”
Section: Discussionunclassified
“…По мере накопления клинических данных были описаны пациенты, рожденные в головном предлежании без сопутствующей гипоксии или рожденные путем кесарева сечения [6]. В настоящий момент высокий процент ягодичного предлежания среди пациентов с гипопитуитаризмом объ- ясняют врожденным дефицитом гормонов аденогипофиза или дефицитом других факторов, приводящих к снижению двигательной активности плода [6]. При проведении генетических исследований среди пациентов с синдромом «разрыва» воронки гипофиза мутации в генах, участвующих в эмбриональном развитии гипофиза, выявляются крайне редко.…”
Section: Discussionunclassified